Conflict Management Approaches in Education : A Systematic Literature Study with the PRISMA Method - Afina Fidaroin Naja; Ali Abakar Ben Abakar; Hakiroh Juwadelia; Muhammad Sholeh; Syunu Trihantoyo (al-Afkar, Journal For Islamic Studies, 2025)
Conflict in educational settings is a natural phenomenon that requires effective management to create a conducive learning climate. This research analyzes conflict management approaches in education through a systematic literature review using the PRISMA method. Data were retrieved from Google Scholar using Publish or Perish (PoP), resulting in 200 articles. After selection, the last 15 articles of the last 5 years were selected as the sample through identification, screening, and eligibility processes. Results showed conflicts arose due to differences in values, ineffective communication, unfair distribution of resources, and academic pressure. A collaborative approach involving all stakeholders (teachers, students, parents, school management) is effective in resolving conflicts constructively. Conflict has a dual impact: it can drive innovation or reduce productivity if unmanaged. A systematic process-from problem identification to solution evaluation-is key to success. Bruce Tuckman's team development model (Forming, Storming, Norming, Performing, Adjourning) emphasizes conflict as a natural stage that strengthens teamwork. In conclusion, effective conflict management not only resolves problems, but also optimizes the potential of conflict as an opportunity for the development of educational institutions. Practical recommendations include conflict resolution training, collaborative approaches, and strengthening communication between parties for a harmonious and productive learning environment.